Pengaruh Kualitas Produk, Kepercayaan, Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pengguna Smartphone Samsung (Studi Kasus Mahasiswa Di Universitas Muhammadiyah Surakarta) - Ambarsari, Vera Dama, Lukman Hakim, SE., M.Si. se (2017)
This study aims to determine the effect of product quality, trust and customer satisfaction to customer loyalty Samsung smartphone users (case studies student at the University of Muhammadiyah Surkarta). The sample used is the consumer who has ever used a smartphone Samsung to distribute questionnaires as many as 100, and the return of 100 questionnaires. The results of this study indicate that the product quality, trust and customer satisfaction significantly influence customer loyalty. Test the validity of the instrument by comparing the 2 value of r count r table for degree of freedom d (f) = n -k with 0,05.sedangkan alpha reliability test using Cronbach Alpha. The study found that: (1) The product quality has a positive effect on customer loyalty Samsung smartphone users (case studies student at the University of Muhammadiyah Surakarta) is evidenced by the t value of 4,116 and the probability value of 0.000 <0.05. (2) Trust no positive effect on customer loyalty Samsung smartphone users (case studies student at the University of Muhammadiyah Surakarta) is evidenced by the t value of 1,554 and the probability value of 0.123> 0.05. (3) Customer satisfaction has a positive effect on customer loyalty Samsung smartphone users (case studies student at the University of Muhammadiyah Surakarta) is evidenced by the t value of 2,786 and the probability value 0.006 <0.05. This research also obtained the value of the coefficient of determination (R2) of 0.435., That means 43.5% variable customer loyalty can be explained by the independent variables, namely product quality, trust, customer satisfaction, while the remaining 56.5% is explained by variables other than this study